Telechemistry 2.0: Remote monitoring of fluorescent chemical reactions - Chun-Yao Hsu (Elsevier, 2021)
Implementation of the Internet-of-Things in chemistry research has the potential to improve research methodologies. Here, we describe a cloud-integrated real-time laboratory monitoring system for: (i) monitoring reactions involving fluorescent chemical species, and (ii) monitoring laboratory environment for safety purpose. A probe-type fluorescence detection system has been constructed to monitor reactions that involve fluorescent molecules. This device incorporates an in-house-built 3D-printed probe, two optical fibers, a light-emitting diode, a photoresistor, and a microcontroller board (MCB). The MCB relays experimental data to a single-board computer (SBC), which then uploads the data to a cloud-based platform (ThingSpeak) for data storage and visualization. The SBC is also connected to auxiliary sensors to measure relative alcohol vapor concentration, temperature, and humidity at different locations in the laboratory. The device has been validated and tested for its performance by monitoring a fluorescent chemical reaction (synthesis of fluorescent gold nanoclusters) for a period of 12 h.